Análisis Multitemporal Del Cultivo De Banano Durante El Periodo 2000-2023, En El Municipio De Zona Bananera, Magdalena (2023)
Taking into account the problems associated with monocultures such as the loss of biodiversity, depletion of nutrients in the soil, water challenges, environmental impacts generated by the use of agrochemicals and pesticides, displacement of communities, impact on food security and alterations in ecosystems .